PENGEMBANGAN DISTRIBUSI LUXPATI BERBASIS UBUNTU SEBAGAI PENUNJANG PROSES BELAJAR MENGAJAR DI JURUSAN PENDIDIKAN TEKNIK INFORMATIKA - Jeny Femila Devi, Kadek; Resika Arthana, I Ketut; Mahendra Darmawiguna, I Gede (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
Linux distribution is a project which is developed with the objective to organize a set of Linux operating system software and to facilitate in the installation of Linux operating system. Ubuntu is one of the most popular Linux distribution which is used worldwide. With the open source characteristics, Ubuntu is equipped with some standard application which is useful for the user. However both Ubuntu and distro have no specific development for programming , graphic designing and networking purpose.The development of Ubuntu based Luxpati distribution is used to facilitate the teaching and learning process at Jurusan Pendidikan Teknik Informatika by using SDLC (Software Development Life Cycle) and using ADDIE (Analysis, Design, Development, Implementation, and Evaluation). On the Linux Luxpati distribution, there were some application which support the teaching and learningprogram in Jurusan Pendidikan Teknik Informatika. This remastering process also included local repository development, new display design, giving new identity, giving additional command in Bahasa Indonesia, and also application for web development.The development of Linux Luxpati was implemented into Ubuntu 12.04.4 LTS with software Remasterys. All functional requirements have been successfully applied based on the design and its implementation into different computer hardware has been tried out successfully.